Sonochemical synthesis of CeVO4 nanoparticles for electrochemical hydrogen storage. (26th January 2022) - Zonarsaghar, Atena; Mousavi-Kamazani, Mehdi; Zinatloo-Ajabshir, Sahar
Abstract: In this study, the synthesis of cerium vanadate (CeVO4 ) nanoparticles using ammonium metavanadate, cerium (III) nitrate hexahydrate as the primary reactant and hydrazine as the source of OH − was presented in the absence and presence of ultrasonic waves. Reaction control was performed using OH − and ethylenediamine sources. Other parameters such as solvent, surfactant, power, and time were also examined. Nanostructures were analyzed by XRD, FESEM, FTIR, DLS, BET, and EDS. FESEM results showed that using ultrasonic irradiation, relatively fine spherical nanoparticles were formed in one step while uniform spherical nanostructures were formed in a two-step path. The obtained product was used for electrochemical storage of hydrogen. The discharge capacity of spherical nanoparticles of CeVO4 with high uniformity was recorded at about 4299 mAh/g. Highlights: CeVO4 nanoparticles were successfully synthesized in the absence and presence of ultrasonic waves. Reaction control was performed using hydrazine and ethylenediamine as new reactants. For the first time, CeVO4 nanoparticles were evaluated for electrochemical hydrogen storage. The discharge capacity of spherical nanoparticles of CeVO4 with high uniformity was recorded at about 4299 mAh/g. Morphological change is one of the effective factors in increasing the yield and storage efficiency.